Right of Progeny and Cairo Declaration of Human Rights in Islam - Ashfaq, Haleema; Pakeeza, Shahzadi (Journal of Islamic and Religious Studies, 2017)
The first main objective of Maqasid I Shari`ah is the completion of human’s necessity; in which protection of progeny (nasl) is the foremost purpose. The preservation of lineage is greatly emphasized by the Islamic Shariah and the Cairo declaration of human rights in Islam also supported the protection of lineage in Islam. All the articles of CDHRI covered the five basic human rights mentioned in Maqasid I Shariah. The research is focused on delineating the concept of protection of lineage as one of the main objective of Shariah and it is supported by evidences from Cairo Declaration of Human Rights in Islam along with Quranic verses and traditions of the Holy Prophet (S.A.W). The aspects covered in the paper range from discussion of right of progeny as well as equal rights of progeny for male and female; rights of children with the hierarchy of their rights from the stage of fetus, having proper nursing, caring, education and a healthy beginning of life. The comparative analysis based on arguments of Shariah and the CDHRI proves that it is the basic objective of Shariah to protect all fundamental rights and right of progeny has the foremost significance in it.